Lucifer as Morning Star: A Theological and Linguistic Analysis of 2 Peter 1:19 - Umaru, Isaac John (Kwaghe International Journal of Arts, Humanities and Religious Studies, 2025)
This study offers a critical examination of the term Lucifer in 2 Peter 1:19, challenging its conventional association with Satan by analysing its linguistic, theological, and historical dimensions. While Lucifer has become synonymous with the fallen angel in Christian tradition—primarily through its use in Isaiah 14:12 in the Latin Vulgate—its appearance in 2 Peter reflects a distinct and positive symbolism. Derived from the Greek word phōsphoros, meaning “light-bringer” or “morning star,” Lucifer in this Petrine context functions as a metaphor for Jesus Christ, whose spiritual illumination rises within the hearts of believers as a sign of eschatological hope. Through a comparative analysis of biblical texts, classical Latin usage, and patristic commentary, the paper demonstrates that the term Lucifer in 2 Peter was never intended to denote evil. Jerome’s translation in the Vulgate aligns with classical Latin conventions, where lucifer referred to Venus as the morning star, a symbol of light and renewal. Church Fathers such as Origen and Jerome themselves acknowledged this Christological reading and distinguished it from the polemical interpretation found in Isaiah. Modern scholarship further supports this view by emphasizing the apocalyptic and transformative imagery embedded in the verse. By disentangling the semantic evolution of Lucifer and situating it within its proper exegetical framework, this study reclaims its original theological intent and argues that Lucifer in 2 Peter 1:19 represents not a demonic figure, but the radiant presence of Christ guiding believers through spiritual darkness toward divine revelation. This reevaluation contributes to broader discussions on biblical translation, doctrinal development, and the symbolic language of Christian eschatology.